2011
DOI: 10.2147/ijn.s23834
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution and pharmacokinetics of 188Re-liposomes and their comparative therapeutic efficacy with 5-fluorouracil in C26 colonic peritoneal carcinomatosis mice

Abstract: Background Nanoliposomes are designed as carriers capable of packaging drugs through passive targeting tumor sites by enhanced permeability and retention (EPR) effects. In the present study the biodistribution, pharmacokinetics, micro single-photon emission computed tomography (micro-SPECT/CT) image, dosimetry, and therapeutic efficacy of 188 Re-labeled nanoliposomes ( 188 Re-liposomes) in a C26 colonic peritoneal carcinomatosis mouse model wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Eight papers were identified exploring the use of drug-eluting beads (drug loading vessels that can prolong drug release) [53] and nanoparticles, nanoliposomes, microspheres, or micelles (which increase drug specificity by being internalized by tumour cells) [43, 47, 57, 63, 7072]. Intraperitoneally placed doxorubicin and mitoxenone drug-eluting beads were shown to continuously release the drug in lower concentrations decreasing side effects and mortality [53] with a similar decline in tumour load compared to free drug.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight papers were identified exploring the use of drug-eluting beads (drug loading vessels that can prolong drug release) [53] and nanoparticles, nanoliposomes, microspheres, or micelles (which increase drug specificity by being internalized by tumour cells) [43, 47, 57, 63, 7072]. Intraperitoneally placed doxorubicin and mitoxenone drug-eluting beads were shown to continuously release the drug in lower concentrations decreasing side effects and mortality [53] with a similar decline in tumour load compared to free drug.…”
Section: Resultsmentioning
confidence: 99%
“…Due to enhanced permeability and retention in tumour cells, nanoliposomes can achieve selective uptake by tumour cells, increasing antitumour efficacy whilst minimising collateral side effects [73]. In one study, it was found that drug delivery using IV 188Re-liposomes increased survival by 34% ( p < 0.05) and decreased tumour volume and ascites by 63.4% and 83.3%, respectively, at 7 days after treatment in mice ( p < 0.05) [70]. In 2007, a phase I study using PLC (doxorubicin encapsulated in liposomes) as part of the HIPEC regime in 29 patients found nanoliposomes to be well tolerated, resulting in a more favourable side effect profile and overall survival of 30.6 months [72].…”
Section: Resultsmentioning
confidence: 99%
“…Single-photon emission computed tomography (SPECT), one of the most important radionuclide-based imaging techniques, has shown great value in tumor imaging 1114. Meanwhile, a number of therapeutic radionuclides have been widely used for tumor treatment, including but not limited to iodine-131 ( 131 I), rhenium-188 ( 188 Re), yttrium-90 ( 90 Y), lutetium-177 ( 177 Lu), and radium-223 ( 223 Ra) 1521. Among these therapeutic radionuclides, 131 I has been routinely used in radionuclide therapy and imaging of thyroid diseases, such as thyroid cancer, because of its high affinity for the thyroid and relatively long half-life (8.01 days).…”
Section: Introductionmentioning
confidence: 99%
“…Various tumor models consistently demonstrate the therapeutic and synergistic combination effects of 188 Re-liposome with chemotherapeutics, including subcutaneously inoculated murine CT26 [28, 31], human LS-174 T [30], and a murine C26 colon carcinoma ascites model [27, 29]. Tumor growth is suppressed, survival time is increased [27, 29, 32], and there is a synergistic chemo/radiotherapeutic [28] effect in various tumor-bearing mice. The efficacy of 188 Re-liposome as a nano-targeted radiotherapeutic has been demonstrated to be greater than that of the chemotherapeutics, Lipo-Dox [27, 28], 5-FU [2931], and sorafenib [32].…”
Section: Introductionmentioning
confidence: 99%
“…Tumor growth is suppressed, survival time is increased [27, 29, 32], and there is a synergistic chemo/radiotherapeutic [28] effect in various tumor-bearing mice. The efficacy of 188 Re-liposome as a nano-targeted radiotherapeutic has been demonstrated to be greater than that of the chemotherapeutics, Lipo-Dox [27, 28], 5-FU [2931], and sorafenib [32]. Preclinical toxicity studies did not show any discernible toxicity in either mice [31] or rats [33, 34].…”
Section: Introductionmentioning
confidence: 99%